Challenges and Strategies for Breeding Resistance in Capsicum annuum to the Multifarious Pathogen, Phytophthora capsici - Derek W. Barchenger; Kurt H. Lamour; Paul W. Bosland (Frontiers in Plant Science, 2018)
Phytophthora capsici is the most devastating pathogen for chile pepper production worldwide and current management strategies are not effective. The population structure of the pathogen is highly variable and few sources of widely applicable host resistance have been identified. Recent genomic advancements in the host and the pathogen provide important insights into the difficulties reported by epidemiological and physiological studies published over the past century. This review highlights important challenges unique to this complex pathosystem and suggests strategies for resistance breeding to help limit losses associated with P. capsici.